2007
DOI: 10.1065/jss2008.03.279
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning characteristics of PAHs between sediment and water in a shallow lake

Abstract: tory conditions, suggesting that the measured pore water PAH concentrations were lower than those predicted. That is to say, not all the sediment PAHs can be available to partition rapidly into sediment pore waters. A variation in soot content is a possible reason. Furthermore, concentrations of PAHs on SPM were higher than those in sediments. The compositions of PAHs on SPM and in sediments were similar, indicating the importance of re-suspension process of sediments in the partitioning process of the shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 35 publications
(44 reference statements)
1
30
1
1
Order By: Relevance
“…Many studies also showed that K oc values of hydrophobic contaminants in suspended particulates or sediments were closely related to their K ow values (Qiao et al 2008;Karickhoff 1981;Chu and Chan 2000). It is widely acknowledged that K DOC is also closely related to K ow (Burkhard 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies also showed that K oc values of hydrophobic contaminants in suspended particulates or sediments were closely related to their K ow values (Qiao et al 2008;Karickhoff 1981;Chu and Chan 2000). It is widely acknowledged that K DOC is also closely related to K ow (Burkhard 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of the fundamental processes controlling the transport, transformation of organic contaminants, especially for hydrophobic organic compounds in aquatic environments is the partitioning and distribution between water, DOC, and POC (Qiao et al 2008;Servos and Muir 1989;Zhou and Rowland 1997). Contaminants can exist in freely dissolved, DOC-bound, POC-bound, sedimentassociated, and biota-associated forms in aquatic systems.…”
Section: Background Aim and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Water samples were collected within 20 min after dosing and analyzed to confirm BaP concentrations from each exposure container. The detailed protocol for sample extracting and BaP concentrations analysis in the exposure water were according to previous study from our laboratory (Qiao et al, 2008). BaP was not detected in any of the acetone treated group.…”
Section: Bap Determination In Exposure Watermentioning
confidence: 99%
“…We also conducted a target analysis for PAHs in water and sediments of selected sampling sites using a traditional target analytical method described in Qiao et al (2008). The detailed results are listed in Tables S7 and S8.…”
Section: Oms Reported Beforementioning
confidence: 99%